2019
DOI: 10.1093/schbul/sby110
|View full text |Cite
|
Sign up to set email alerts
|

Beyond Trauma: A Multiple Pathways Approach to Auditory Hallucinations in Clinical and Nonclinical Populations

Abstract: That trauma can play a significant role in the onset and maintenance of voice-hearing is one of the most striking and important developments in the recent study of psychosis. Yet the finding that trauma increases the risk for hallucination and for psychosis is quite different from the claim that trauma is necessary for either to occur. Trauma is often but not always associated with voice-hearing in populations with psychosis; voice-hearing is sometimes associated with willful training and cultivation in noncli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
51
3
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(60 citation statements)
references
References 83 publications
3
51
3
3
Order By: Relevance
“…We inferred that the improvement of auditory hallucination severity can decrease the mood disturbances evoked by obstacles to social interaction; furthermore, because of the negative impact of the severity of auditory hallucinations on the severity of depressive symptoms (Chiang et al 2018;Connor & Birchwood 2013), improvement in the severity of auditory hallucinations can result in positive changes in this relationship. Previous studies confirm that social interaction can lead to depression in people diagnosed with schizophrenia (Luhrmann et al 2019). However, few studies have investigated the influence of psychotic symptoms in this process.…”
Section: The Mediating Effect Of Auditory Hallucinations On Social Inmentioning
confidence: 99%
See 2 more Smart Citations
“…We inferred that the improvement of auditory hallucination severity can decrease the mood disturbances evoked by obstacles to social interaction; furthermore, because of the negative impact of the severity of auditory hallucinations on the severity of depressive symptoms (Chiang et al 2018;Connor & Birchwood 2013), improvement in the severity of auditory hallucinations can result in positive changes in this relationship. Previous studies confirm that social interaction can lead to depression in people diagnosed with schizophrenia (Luhrmann et al 2019). However, few studies have investigated the influence of psychotic symptoms in this process.…”
Section: The Mediating Effect Of Auditory Hallucinations On Social Inmentioning
confidence: 99%
“…The overall profile of more masculine, dominant, powerful, and negatively personified voices in people diagnosed with schizophrenia clearly evokes higher levels of distress (Badcock & Chhabra ). Luhrmann et al () employed ethnographic method to explore different phenomenological patterns for voice‐hearing, which may reflect the different trauma experience for those who hear voices. The auditory hallucinatory experience might play a console function in the context of trauma.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is a complex story. Biological affordance, genetic predisposition, life experience, and cultural invitation all seem to interact to shape the experience of hallucination-like events (Luhrmann et al 2019).…”
Section: Note Julian Kiverstein and Erik Rietveld Are Supported By Tmentioning
confidence: 99%
“…Accumulating evidence suggests that dissociation accounts for some of the heterogeneity in high hypnotic suggestibility (Dell, 2009;Terhune & Cardeña, 2015). Indeed, high dissociative highly suggestible (HDHS) individuals are more responsive to hypnotic suggestions for hallucinations than low dissociative highly suggestible (LDHS) individuals and are also characterized by an elevated propensity for dissociative states and previous exposure to stressful life events (Terhune, Cardeña, & Lindgren, 2011), both of which reliably covary with hallucination-proneness in clinical and nonclinical samples (Bailey et al, 2018;Fassler et al, 2006;Irwin, Schofield, & Baker, 2014;Luhrmann et al, 2019;Pilton, Varese, Berry, & Bucci, 2015). Previous research has found an interaction between hypnotic suggestibility and dissociation in the reporting of anomalous experiences, with both variables related to anomalous experiences, including hallucinations, particularly when in conjunction (Pekala, Kumar, & Marcano, 1995).…”
Section: Introductionmentioning
confidence: 99%